Specification and spatial arrangement of cells in the germline stem cell niche of the Drosophila ovary depend on the Maf transcription factor Traffic jam - Panchal, Trupti (PLoS Genet, 2017)
Germline stem cells in the Drosophila ovary are maintained by a somatic niche. The niche is structurally and functionally complex and contains four cell types, the escort, cap, and terminal filament cells and the newly identified transition cell. We find that the large Maf transcription factor Traffic jam (Tj) is essential for determining niche cell fates and architecture, enabling each niche in the ovary to support a normal complement of 2–3 germline stem cells. In particular, we focused on the question of how cap cells form. Cap cells express Tj and are considered the key component of a mature germline stem cell niche. We conclude that Tj controls the specification of cap cells, as the complete loss of Tj function caused the development of additional terminal filament cells at the expense of cap cells, and terminal filament cells developed cap cell characteristics when induced to express Tj. Further, we propose that Tj controls the morphogenetic behavior of cap cells as they adopted the shape and spatial organization of terminal filament cells but otherwise appeared to retain their fate when Tj expression was only partially reduced. Our data indicate that Tj contributes to the establishment of germline stem cells by promoting the cap cell fate, and controls the stem cell-carrying capacity of the niche by regulating niche architecture. Analysis of the interactions between Tj and the Notch (N) pathway indicates that Tj and N have distinct functions in the cap cell specification program. We propose that formation of cap cells depends on the combined activities of Tj and the N pathway, with Tj promoting the cap cell fate by blocking the terminal filament cell fate, and N supporting cap cells by preventing the escort cell fate and/or controlling the number of cap cell precursors.